(x+2)(5x-4)=0

Simple and best practice solution for (x+2)(5x-4)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+2)(5x-4)=0 equation:


Simplifying
(x + 2)(5x + -4) = 0

Reorder the terms:
(2 + x)(5x + -4) = 0

Reorder the terms:
(2 + x)(-4 + 5x) = 0

Multiply (2 + x) * (-4 + 5x)
(2(-4 + 5x) + x(-4 + 5x)) = 0
((-4 * 2 + 5x * 2) + x(-4 + 5x)) = 0
((-8 + 10x) + x(-4 + 5x)) = 0
(-8 + 10x + (-4 * x + 5x * x)) = 0
(-8 + 10x + (-4x + 5x2)) = 0

Combine like terms: 10x + -4x = 6x
(-8 + 6x + 5x2) = 0

Solving
-8 + 6x + 5x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(-2 + -1x)(4 + -5x) = 0

Subproblem 1

Set the factor '(-2 + -1x)' equal to zero and attempt to solve: Simplifying -2 + -1x = 0 Solving -2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -1x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -1x = 0 + 2 -1x = 0 + 2 Combine like terms: 0 + 2 = 2 -1x = 2 Divide each side by '-1'. x = -2 Simplifying x = -2

Subproblem 2

Set the factor '(4 + -5x)' equal to zero and attempt to solve: Simplifying 4 + -5x = 0 Solving 4 + -5x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -5x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -5x = 0 + -4 -5x = 0 + -4 Combine like terms: 0 + -4 = -4 -5x = -4 Divide each side by '-5'. x = 0.8 Simplifying x = 0.8

Solution

x = {-2, 0.8}

See similar equations:

| 2x^2=3+9x | | 7x-6=3x+14 | | 10e+2e-9=39 | | 10x-15=6x+30 | | 4x+6=91 | | (x-8)(5x-4)=0 | | 4y+12=6y+14 | | 12j=16j(j-8) | | (3w-4)(4w+6)= | | 3x-2(-5x+3)=72 | | 7+2(7)=30 | | h=0.5s-5 | | 20-5w=60 | | 6-10m=-54 | | 8-3p=-14 | | X+3y=-15 | | 2v^2-14v=0 | | 2+4n=-10 | | 1x-4x=6 | | 10=-5(3+w) | | 7-2n=5 | | 23x-16871=1000 | | 7(10w+1)= | | (x+2)(x-8)(5x-4)=0 | | 9xy^2+4y-13=0 | | (x-3)=-3x+33 | | 15x+9= | | 24=3-7x | | 2b+2=3p-7 | | 3x-2=2x+13 | | -12x+3=-8x-6 | | (k+4)=7 |

Equations solver categories